2013
DOI: 10.1071/ah13125
|View full text |Cite
|
Sign up to set email alerts
|

The role of boards in clinical governance: activities and attitudes among members of public health service boards in Victoria

Abstract: Objectives. To determine the nature and extent of governance activities by health service boards in relation to quality and safety of care and to gauge the expertise and perspectives of board members in this area.Methods. This study used an online and postal survey of the Board Chair, Quality Committee Chair and two randomly selected members from the boards of all 85 health services in Victoria. Seventy percent (233/332) of members surveyed responded and 96% (82/85) of boards had at least one member respond.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…With respect to skills and expertise, our findings echo messages from previous studies in the USA,11 the UK23 and Australia,24 indicating that (additional) board training on quality governance would be useful. Such training should be accessible, flexible and tailored rather than assuming that ‘one size fits all’.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…With respect to skills and expertise, our findings echo messages from previous studies in the USA,11 the UK23 and Australia,24 indicating that (additional) board training on quality governance would be useful. Such training should be accessible, flexible and tailored rather than assuming that ‘one size fits all’.…”
Section: Discussionsupporting
confidence: 78%
“…While some health service boards in Victoria had high aspirations and clear plans to improve care quality, others appeared to be ‘muddling through’. This resonated with findings from our earlier survey of board members from all 85 health service boards in Victoria,24 where wide variation was evident in the nature and extent of relevant activities being undertaken at the board level.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…One aspect of this is board agendas and the extent to which patient safety is discussed at board meetings. 73,74 Findings from US hospital settings suggest that having quality and safety as standing items on the board agenda provides a critical lever for engagement in quality and safety issues.…”
Section: Internal Board Oversightmentioning
confidence: 99%
“…73,74 Some of this work has revealed the limited time and resources that many boards devote to such activities. US and Canadian research found a 'remarkably low' degree of knowledge among hospital boards about published quality reports and best-practice guidance in relation to safe care, 66 with many board members having only limited expertise in using and implementing such information.…”
Section: Measuring Safe Carementioning
confidence: 99%